Pengaruh Pengaruh Pengendalian Internal, Tekanan dan Kesesuaian Kompensasi terhadap Kecenderungan Kecurangan (Fraud) - Nelam Sari, Oriza Sativa; Syofyan, Efrizal (Jurnal Eksplorasi Akuntansi, 2025)
This study examines the impact of internal control, financial pressure, and compensation fairness on fraudulent tendencies, focusing on convicted corruption offenders in Padang City. The research framework is based on the Fraud Triangle Theory, which identifies pressure, opportunity, and rationalization as the primary drivers of fraudulent behavior. A robust internal control system is essential for mitigating fraud risk, ensuring financial reporting integrity, and safeguarding organizational assets. Furthermore, excessive financial pressure and perceived unfair compensation can exacerbate an individual’s likelihood of engaging in fraudulent activities. The findings of this study contribute to the academic discourse on fraud in accounting and provide practical insights for policymakers, corporations, and regulatory bodies. Strengthening internal controls and addressing financial pressures within organizations can serve as effective measures to prevent fraud, enhance financial transparency, and uphold ethical standards in financial management.